Behaviour of Sarawak Clayey Soil using Various By-Product Additives Stabiliser for Potential Subgrade Materials - Striprabu, A/L Strimari (Universiti Malaysia Sarawak (UNIMAS), 2018)
Due to rapid development and scarcity of land with good and desirable soil for civil infrastructure, the development projects shifted to the site with problematic soil such as soft soil. Construction of pavement subgrade layer with soft soil is hampered by their low strength and high deformability which causes difficulties such as stability deficiency and high settlements which exhibit insufficient strength to support the pavement traffic loading. Chemical stabilisation of clay soils in Sarawak using Fly Ash (FA), Rice Husk Ash (RHA) and Palm Oil Fuel Ash (POF A) was carried out due to their potential benefit to improve engineering properties of weak subgrade soil through cementitious products. Three different soils from Sri Arnan, Serian and Kuching divisions were collected and considered in this study to represent a range of subgrade soil in Sarawak based on different clay content. All tested clay soils are categorised as high plasticity silty clay.